Anayasal dilin semantiği üzerine : Anayasanın ruhu kavramı - Fertellioğlu, Buğrahan (My University, 2019)
Bu çalışmada anayasanın ruhu kavramı özelinde anayasal dilin semantiğiincelenmiştir. Çalışmanın temel motivasyonu, incelenen kavramın genel kullanımı ileAnayasa metnindeki işlevinin birbiriyle örtüşmemesi olmuştur. Çalışmanın birincibölümünde, anayasa normlarının geçerliliğini farklı şartlara bağlayan iki düşünürün teorilerikarşılıklı olarak incelenmiştir. Carl Schmitt ve Hans Kelsen’in teorilerine yer verilen bubölümde, farklı geçerlilik anlayışlarına göre ortaya konan anayasa tanımlarına bağlı olarakanayasanın ruhu ve ona benzer çekirdek yapıların ne şekilde kavranabileceği tartışılmıştır.Kavramın teorik açıdan incelenmesinden sonra, çalışmanın ikinci bölümünde Türk AnayasaHukuku özelinde bir inceleme yapılmıştır. Bu bölümde 1961 Anayasası ile anayasa metninegiren kavramın anayasal niteliği merkeze alınmış; düzenlemeler, temel yaklaşımlar veAnayasa Mahkemesi Kararları incelenmiştir. Otantik tanım girişimlerinin birinci bölümdesunulan teorik çerçeve bakımından ne şekilde değerlendirilebileceği tartışılmış ve istikrarlı birtanımlamanın imkânları sorgulanmıştır. Çalışmanın sonunda, incelenen kavramın ulusalsistemdeki kendine özgü nitelikleri ortaya konmuş ve özellikle anayasanın sözü-anayasanınruhu ikiliğinin yorum sürecinde neden olduğu güçlükler tartışılmıştır.

In this study, the semantics of the constitutional language was examined in terms ofthe concept of the spirit of constitution. The main motivation of the study was that the generalusage of the concept examined did not overlap with the function in the Constitution of theRepublic of Turkey. In the first section of the study, the theories of the two philosophers whotheorize the validity of the constitutional norms in different manners were examined mutually.In this section which includes the theories of Carl Schmitt and Hans Kelsen, how the spirit ofconstitution and other similar structures can be understood depend on different definitions ofconstitution according to these different conceptualizations was discussed. After thetheoretical examination of the concept, in the second section of the study, the spirit ofconstitution was analyzed in the context of the Turkish Constitutional Law. The constitutionbased character of the concept which appeared in the 1961 Constitution for the first time wasfocused and histories of constitutional amendments, basic approaches and case law of theTurkish Constitutional Court were studied. Additionally, the ways in which authenticdefinition initiatives can be evaluated in terms of theoretical framework presented in the firstsection were discussed and it has been questioned whether a stable definition is possible. Atthe end of the study, distinctive characters of the concept in the domestic system wereestablished and the difficulties in interpretation caused by the duality of “the letter of theconstitution-the spirit of the constitution” in the Constitution of the Republic of Turkey werediscussed.
Keywords: Anayasa hukuku; anayasa normlarının geçerliliği The spirit of constitution; anayasal dil; anayasal yorum; Anayasanın ruhu; constitutional interpretation; constitutional language; Constitutional law; Hukuk; Law; validity of constitutional norms